Quantum Chemical and Experimental Studies of an Unprecedented Reaction Pathway of Nucleophilic Substitution of 2-Bromomethyl-1,3-thiaselenole with 1,3-Benzothiazole-2-thiol Proceeding Stepwise at Three Different Centers of Seleniranium Intermediates - Svetlana V. Amosova (MDPI AG, 2021)
The results of quantum chemical and experimental studies of the reaction of 2-bromomethyl-1,3-thiaselenole with 1,3-benzothiazole-2-thiol made it possible to discover the unprecedented pathway of this reaction, which proceeds stepwise at three different centers of seleniranium intermediates. The first stage includes an attack of thiolate anion at the selenium atom of the seleniranium cation accompanied by ring opening with the formation of (Z)-2-[(1,3-benzothiazol-2-ylsulfanyl)selanyl]ethenyl vinyl sulfide, which is converted to six-membered heterocycle, 2-(2,3-dihydro-1,4-thiaselenin-2-ylsulfanyl)-1,3-benzothiazole, in a 99% yield. The latter compound undergoes rearrangement with ring contraction producing five-membered heterocycle, 2-[(1,3-thiaselenol-2-ylmethyl)sulfanyl]-1,3-benzothiazole, in a 99% yield (the thermodynamic product). The formation of 1,2-bis[(Z)-2-(vinylsulfanyl)ethenyl] diselenide is the result of the disproportionation of (Z)-2-[(1,3-benzothiazol-2-ylsulfanyl)selanyl]ethenyl vinyl sulfide. Thus, based on the quantum chemical and experimental studies, a regioselective synthesis of the reaction products in high yields was developed.